2022
DOI: 10.3389/fmicb.2022.935688
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and clinical characteristics of human bocavirus infection in children hospitalized for acute respiratory tract infection in Qingdao, China

Abstract: Persistent infection and prolonged shedding of human bocavirus 1 (HBoV1) in children have been reported, and the role of HBoV1 as a sole causative pathogen in acute respiratory infection (ARI) is yet to be established. While the reported prevalence of HBoV infection varies due to different detection methods and sampling criteria, determining the viral and bacterial etiology of HBoV infection using multiplex real-time PCR is yet to be reported. Herein, we aimed to further explore the pathogenicity of HBoV in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(26 citation statements)
references
References 68 publications
(82 reference statements)
4
22
0
Order By: Relevance
“…Several clinical studies have identified HBoV1 as one of the most detected respiratory viruses in young children with RTIs and, as with other respiratory viruses, it is widespread in both low- and high-income countries [ 1 , 2 , 3 ]. Most studies showed a higher prevalence in males [ 1 , 4 , 5 , 6 , 7 , 8 , 9 ], others did not find any sex predominance [ 10 ], and a few showed a slightly higher prevalence among females [ 3 , 11 , 12 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 4 more Smart Citations
“…Several clinical studies have identified HBoV1 as one of the most detected respiratory viruses in young children with RTIs and, as with other respiratory viruses, it is widespread in both low- and high-income countries [ 1 , 2 , 3 ]. Most studies showed a higher prevalence in males [ 1 , 4 , 5 , 6 , 7 , 8 , 9 ], others did not find any sex predominance [ 10 ], and a few showed a slightly higher prevalence among females [ 3 , 11 , 12 ].…”
Section: Epidemiologymentioning
confidence: 99%
“…Most literature reported HBoV infection as prevalent in children between 6 months and 2 years with the highest detection rate during the second year [ 4 , 6 , 10 , 12 , 13 , 14 ], while it is rare (<5%) during the first 6 months of life [ 15 , 16 ]. Only in the study by Wang et al were children > 5 years the most affected, followed by children < 2 years and infants [ 1 , 15 , 16 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 3 more Smart Citations